Transformations récentes de l’agglomération québécoise : fonctions, population et organisation de l’espace - Trotier, Louis (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1962)
Over the last ten years the Québec City agglomeration has been subject to numerous transformations despite the city's rather mediocre economic development and a rate of increase of population which is lower than that of most large cities of Canada. These transformations present differing characteristics in the various sectors of the city and of its suburbs.The central zone of the agglomeration, where the population is decreasing, has been the locale of rather extensive urban renewal despite the many problems posed by historic buildings and an outmoded lot structure. A second zone, termed « peripheral » by the writer, contains the areas exhibiting the greatest increase of population of the agglomeration ; this zone is characterised by a disorderly spatial structure, typical of recently urbanised areas. Finally, the third zone, termed sub-urban, gives the appearance of having been subjected to the minimum amount of change. Here, however, farms are rapidly disappearing as a result of land speculation and incipient urbanisation.